Eksistensi Pondok Pesantren Hidayatul Mubtadiin II Simpang Mesuji - Makrufah, Nining; Fakhri, Jamal; Abbas, Erjati (Attractive : Innovative Education Journal, 2024)
The existence of Islamic boarding schools always changes according to societal developments. Islamic boarding schools that grow and develop in the midst of society, in social processes and interactions with society cannot be avoided. Islamic boarding school activities and participation always take part in building society, requiring new ideas and knowledge. Islamic boarding schools are not only active in providing knowledge to the public in terms of religious knowledge, but also try to improve the standard of living and culture in harmony with Islamic teachings. This type of research is field research, that is, research carried out directly in the field or on respondents. The research approach used is a qualitative approach. The purpose of this research is to describe a situation or event. The data collection techniques used are the observation method, interview method and documentation method. The data analysis technique in this research uses data collection, data reduction, data presentation, and drawing conclusions. The results of the research are that the existence of the Hidayatul Mubtadi’in II Simpang Mesuji Islamic Boarding School has a relationship between the Islamic boarding school and the surrounding community. The relationship is well established. Even though the number of students has decreased, the Hidayatul Mubtadi’in II Simpang Mesuji Islamic boarding school continues to strive to exist and play a role in accordance with the vision and mission that have been instilled in the Islamic boarding school. Keywords: Pesantren, Existention Pesantren, Modern Era